2021
DOI: 10.1016/j.neo.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

A combinatorial drug screen in PDX-derived primary rhabdomyosarcoma cells identifies the NOXA - BCL-XL/MCL-1 balance as target for re-sensitization to first-line therapy in recurrent tumors

Abstract: First-line therapy for most pediatric sarcoma is based on chemotherapy in combination with radiotherapy and surgery. A significant number of patients experience drug resistance and development of relapsed tumors. Drugs that have the potential to re-sensitize relapsed tumor cells toward chemotherapy treatment are therefore of great clinical interest. Here, we used a drug profiling platform with PDX-derived primary rhabdomyosarcoma cells to screen a large drug library for compounds re-sensitizing relapse tumor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…It is crucial to conduct studies using PDX before conducting clinical studies in humans, since PDX models closely mimic the essential features of patients' tumors. Although limited research has been carried out on PDX in RMS, a study by Manzella et al found that a subgroup of RMS was highly sensitive to AKT inhibitors and that NOXA-BCL-XL/MCL-1, which are crucial molecules in the mitochondrial apoptotic cascade, could be targeted therapeutically to modulate the drug response in RMS using the PDX model (21,22). However, the current study is the first to use PDX to evaluate redox regulation in RMS.…”
Section: Discussionmentioning
confidence: 81%
“…It is crucial to conduct studies using PDX before conducting clinical studies in humans, since PDX models closely mimic the essential features of patients' tumors. Although limited research has been carried out on PDX in RMS, a study by Manzella et al found that a subgroup of RMS was highly sensitive to AKT inhibitors and that NOXA-BCL-XL/MCL-1, which are crucial molecules in the mitochondrial apoptotic cascade, could be targeted therapeutically to modulate the drug response in RMS using the PDX model (21,22). However, the current study is the first to use PDX to evaluate redox regulation in RMS.…”
Section: Discussionmentioning
confidence: 81%
“…A previous study demonstrated the survival of a cell subpopulation expressing MYOD1 in an RMS cell line following treatment with the standard-of-care chemotherapeutic agents vincristine and doxorubicin [7]. Other studies have shown high levels of antiapoptotic proteins are present in treatment-refractory RMS tumors [8,9] and upregulation of selective signaling pathways (e.g., GP130/STAT and Hedgehog) in chemotherapy-resistant RMS cells [10,11]. Recently, a study by Patel et al demonstrated that chemotherapy eliminates proliferative myoblast-like cells in the FN embryonal subtype of RMS (ERMS), leaving behind an immature cell population that recapitulates paraxial mesodermal cells in development [12].…”
Section: Introductionmentioning
confidence: 98%
“…High expression of anti-apoptotic BCL-2 family protein members has also been reported for RMS [93][94][95] and preclinical testing of BH3-mimetics as singleagents or in combination with other drugs has shown efficacy in RMS [96][97][98] .…”
Section: Programmed Cell Death Mechanisms In Rmsmentioning
confidence: 99%